Parkett : The Parkett series with contemporary artists (Zürich : Parkett-Verlag, 1996)
Table of Content Penta’s Parabolas by Juri Steiner Tony Oursler A Conversation in the Green Room with Tony Oursler, Tracy Leipold & Louise Neri Tony Oursler’s Alters by Lynne Cooke Like Water by Frances Richard Raymond Pettibon A Conversation with Jim Lewis The Drawing Rescues Poetry by Boris Groys Untitled by Hilton Als Surfing with Raymond by Ralph Rugoff Raymond Pettibon Reads by Thyrza Nichols Goodeve Thomas Schütte Thomas Schütte by Adrian Searle A Public for the Space by Bartomeu Mari Lily Lies by Hans Rudolf Reust Lost at Sea by Neville Wakefield Installations by Ulrich Look Schütte’s Innocents by Elizabeth Janus Zoe Leonard & Cheryl Dunye, Insert Juggling with Gravity – Christoph Rütimann by Max Wechsler Loitering with Intent, Diane Arbus at the Movies, Les Infos du Paradis by Susan Morgan Now You See It, Now You Don’t, The Magic Magic Book, Cumulus from America by Nancy Princenthal A Conversation, Cumulus from Europe, Lionel Bovier & Christophe Cherix.
When a host of peculiar voices rises in chorus, it is time to open wide the doors. Thomas Schütte’s human figures have recently acquired the proportions of science fiction. How real are the envisioned people of the future if they seem to have sprung from collective memory? In any case, we stand before them as we do before Michelangelo’s David. Are myths truer than reality? The INSERT by Zoe Leonard and Cheryl Dunye displays the cogency of documented fiction, or rather fictional documentation, demonstrating once again how effortlessly we believe in the bogus traces of a “public" life, as if it had already become part of our common heritage!. (editorial by publisher)
boek
Keywords: Oursler, Tony; Schütte, Thomas; Pettibon, Raymond